An Analysis of Place Branding to Enhance the Image of Bandung City and its Implications toward the Decisions to Visit Tourism Destination - Hurriyati, Ratih (SOSIOHUMANIKA, 2015)
ABSTRACT: Travelers have a central role as decision-makers to visit a particular tourist destination spot. However, the number of visitors for each destination in Bandung city is relatively fluctuation. It happened because the image of Bandung as a tourist destination is still very weak. Through the efforts of place branding, it is expected to improve the image of Bandung city, not only as a creative industrial area, but at the same time as a tourist destination. The purpose of this study was to determine the overviews of place branding, image of the city, and decision to visit; the effect of place branding toward the decision to visit; the influence on decisions to visit the citys image; the effect of place branding to the image of the city; and the influence of place branding and image of the city simultaneously to the decision to visit. TheÂ method of research is using descriptive verification. Data was collected through interviews, observations, questionnaires, and literature. The results of the study revealed that the implementation of place branding is assessed good enough. The image of Bandung city is rated so towering. While the decisions to visit tourism destination is generally considered lofty. Therefore, Bandung city government needs to provide and develop facilities evenly across tourist destinations, including public transportation. KEY WORD: Travelers, decision to visit, image of Bandung city, place branding implementation, public transportation, and tourism destination.Â RESUME: âSebuah Analisis âMerk Tempatâ untuk Meningkatkan Citra Kota Bandung serta Implikasinya terhadap Keputusan Mengunjungi Destinasi Pariwisataâ. Wisatawan memiliki peran sentral selaku pembuat keputusan untuk mengunjungi suatu tempat destinasi wisata tertentu. Namun, jumlah kunjungan wisata ke setiap destinasi di kota Bandung relatif fluktuatif. Hal itu terjadi karena citra Bandung sebagai destinasi wisata masih sangat lemah. Melalui upaya âmerk tempatâ diharapkan dapat meningkatkan citra kota Bandung, tidak hanya sebagai kawasan idustri kreatif, melainkan sekaligus sebagai tempat destinasi wisata. Tujuan penelitian ini adalah untuk mengetahui gambaran âmerk tempatâ, citra kota Bandung, dan keputusan berkunjung; pengaruh âmerk tempatâ terhadap keputusan mengunjungi; pengaruh citra kota Bandung terhadap keputusan mengunjungi; pengaruh âmerk tempatâ terhadap citra kota; serta pengaruh âmerk tempatâ dan citra kota secara simultan terhadap keputusan mengunjungi. Metode penelitian yang digunakan adalah verifikasi deskriptif. Tehnik pengumpulan data yang digunakan adalah wawancara, observasi, angket, serta studi literatur. Hasil penelitian menunjukkan bahwa pelaksanaan âmerk tempatâ dinilai cukup baik. Citra kota Bandung dinilai sangat tinggi. Sedangkan keputusan mengunjungi destinasi pariwisata secara umum dinilai tinggi. Oleh karena itu, pemerintah kota Bandung perlu menyediakan dan mengembangkan fasilitas secara merata di seluruh destinasi wisata, termasuk alat transportasi umum. KATA KUNCI: Wisatawan, keputusan mengunjungi, citra kota Bandung, implementasi âmerk tempatâ, dan destinasi pariwisata.Â About the Author: Dr. Ratih Hurriyati is a Senior Lecturer at the Doctoral Programme in Management Studies SPs UPI (Graduate School, Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. The author can be contacted via e-mail at: ratih@upi.eduHow to cite this article? Hurriyati, Ratih. (2015). âAn Analysis of Place Branding to Enhance the Image of Bandung City and its Implications toward the Decisions to Visit Tourism Destinationâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.8(1) Mei, pp.99-114. Bandung, Indonesia: Minda Masagi Press, UNHAS Makassar, and UNIPA Surabaya, ISSN 1979-0112. Chronicle of the article: Accepted (March 2, 2014); Revised (July 2, 2014); and Published (May 30, 2015).